(untitled) (Research, Society and Development, 2021)
This is an observational, analytical and cross-sectional study, with a quantitative character, carried out from secondary data from the Notifiable Diseases Information System (SINAN). The objective was to analyze the spatial pattern of cases of suicide attempts by medication in the city of Campina Grande/PB, in 2019. Descriptive statistics were performed, as well as the elaboration of maps (Moran and Lisa) to verify the spatial distribution of cases in study. A choropleth map was also carried out to demonstrate the occurrence and intensity of the phenomenon and a Moran Scattering Diagram, using the Global Moran Index and the Local Moran Index, with the help of the free statistical software The R Project for Statistical Computing. To guide the spatial analysis, the “neighborhood” variable was used. The sample totaled 237 patients residing in the urban area of ​​Campina Grande who attempted suicide through the use of medication. The profile of the patients followed the following pattern: female (79.7%), aged from 20 to 39 years (51.5%), education at elementary level (49.4%), single with marital status (64.5%) and the majority being students (42.2%), followed by unemployed (32.1%). The districts with the highest number of cases were: Malvinas (n=23), Bodocongó (n=21) and Serrotão (n=9). On the other hand, the neighborhoods Mirante, Cuités, Sandra Cavalcante, Louzeiro, Itararé and Velame did not present cases of suicide attempts through the use of medication. Thus, it was found that, in the global aspect, there was no significant spatial autocorrelation in the studied region, with a Global Moran Index found of 0.1210.